STUDENTS’ IDEAS ABOUT TRUST IN INTERETHNIC RELATIONS - A. V. Alborova; S. V. Dreeva (Вестник университета)
The article reviews approaches to understanding the phenomenon of trust in relationships. It is noted that various authors consider trust as the main principle of forming constructive relations in modern society. The paper gives data on the research of the ideas of students of the Republic of North Ossetia – Alania (Ossetians and Russians, aged 15 to 22 years) about trust in interethnic relations. According to the results of the study, students who are representatives of Ossetian nationality most often define trust in interethnic relations as “Acceptance of “foreign” national values, customs and culture”. Russian students understand trust in interethnic relations as “Confidence in assistance and support in a difficult situation from a representative of another ethnic group”. Both groups of students surveyed believe that the willingness of representatives of different ethnic groups to cooperate is important in trusting inter-ethnic relations.